Euripidea tertia - Kovacs, David. (Mnemosyne, Supplements, 2003)
Euripidea Tertia is a companion volume to the Loeb Classical Library edition of Euripides. It discusses places in the text primarily of the late plays where the editor's choice of variants or adoption of conjectures required some explanation and also places where the translation needed explaining. The plays covered are Iphigenia Taurica, Ion, Helen, Phoenissae, Orestes, Bacchae, Iphigenia Aulidensis , and Rhesus , with addenda on earlier plays. Reviewers of the earlier volumes Euripidea and Euripidea Altera have commented on the cogency and sensitivity of his textual arguments. Serious students of Euripides, tragedy, textual criticism, and Greek metre will all want to read this book.